2021
DOI: 10.1038/s41598-021-99842-4
|View full text |Cite
|
Sign up to set email alerts
|

Novel magnetic organic–inorganic hybrids based on aromatic polyamides and ZnFe2O4 nanoparticles with biological activity

Abstract: Magnetic nanoparticles were creatively selected as stable, inexpensive, biodegradable, facile recoverable, and functionalizable supports for a variety of synthetic and natural polymers. Herein, for the first time, aromatic polyamide was synthesized on the magnetic core of zinc iron oxide (ZnFe2O4). Terephthaloyl chloride and derivations of phenylenediamine were employed as monomers in this polymerization process. The toxicity of the synthesized hybrid at the highest concentration (1000 μg/ml) is 13.65% and on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 57 publications
2
14
0
Order By: Relevance
“…According to previous studies, if magnetic nanoparticles are placed in a composite structure, their value of saturation magnetization will be reduced. 27,40 By comparing the saturation magnetization of pure Fe 3 O 4 (which is about 75 emu g −1 ) 27 and the nanobiocomposite (which is about 8.47 emu g −1 ), it can be concluded that magnetic nanoparticles are well placed in the structure of the composite.…”
Section: Vsm Analysismentioning
confidence: 99%
“…According to previous studies, if magnetic nanoparticles are placed in a composite structure, their value of saturation magnetization will be reduced. 27,40 By comparing the saturation magnetization of pure Fe 3 O 4 (which is about 75 emu g −1 ) 27 and the nanobiocomposite (which is about 8.47 emu g −1 ), it can be concluded that magnetic nanoparticles are well placed in the structure of the composite.…”
Section: Vsm Analysismentioning
confidence: 99%
“…Therefore, the development of new antibacterial agents is still a hot research topic. 6,[17][18][19] Micro/ nanocarbon functional materials that can be used as carriers and antibacterial agents in the field of antibacterial dressings have attracted attention from medical staff and researchers. Because these micro/nanocarbons have many advantages including raw materials, low preparation cost, good mechanical stability, strong biocompatibility, biodegradability and antibacterial activity.…”
Section: Introductionmentioning
confidence: 99%
“…The broad peak at 3384 cm −1 in the ZnFe 2 O 4 spectrum is attributed to the vibration stretching of the O–H groups of the water molecules adsorbed on the ZnFe 2 O 4 surface during the hydrothermal synthesis 45 . In addition, two vibration peaks at 1500 cm −1 and 1612 cm −1 are associated with O–H binding, suggesting a large number of hydroxyl groups on the surface of colloidal ZnFe 2 O 4 46 , 47 . The ZC exhibits some peaks at 835 cm −1 (aromatic CH=), 1191–1281 cm −1 (C=C bonds), and 2873 cm −1 (C–H groups).…”
Section: Resultsmentioning
confidence: 99%